2013
DOI: 10.5888/pcd10.120256
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for Improving Nutrition and Physical Activity Behaviors in Adult African American Populations: A Systematic Review, January 2000 Through December 2011

Abstract: IntroductionThe incidence of preventable chronic diseases is disproportionally high among African Americans and could be reduced through diet and physical activity interventions. Our objective was to systematically review the literature on clinical outcomes of diet and physical activity interventions conducted among adult African American populations in the United States.MethodsWe used the Preferred Reporting Items for Systematic Review and Meta Analysis construct in our review. We searched Medline (PubMed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 33 publications
1
46
1
Order By: Relevance
“…Over the course of 12 weeks, BMORe participants' adoption of healthy eating, cooking, and exercise strategies empowered them to overcome initial barriers through lifestyle changes. Similar to other research [1215, 27], this study demonstrated how a nutrition and physical activity intervention within the church environment can effectively decrease health disparities among minority populations including African-American and rural populations.…”
Section: Discussionsupporting
confidence: 83%
“…Over the course of 12 weeks, BMORe participants' adoption of healthy eating, cooking, and exercise strategies empowered them to overcome initial barriers through lifestyle changes. Similar to other research [1215, 27], this study demonstrated how a nutrition and physical activity intervention within the church environment can effectively decrease health disparities among minority populations including African-American and rural populations.…”
Section: Discussionsupporting
confidence: 83%
“…The baseline data were consistent with the literature in that both treatment and comparison participants consumed slightly more than two servings of fruits/vegetables per day [25], perceived their fat consumption as moderate [2224], and had low to moderate physical activity levels [32,37,62]. Clinical results showed that both treatment and comparison groups had BMIs in the obese range, systolic blood pressure at hypertensive levels, and LDL and HDL cholesterol outside of recommended levels [2,9,39,40]. These findings demonstrate that this sample of mid-life and older African Americans have health indicators consistent with the general population of African Americans in this age range and are an appropriate group for an intervention to reduce CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, food choice, dietary quality and physical activity have been shown to influence clinical outcomes in African American adults such as BMIs, girth circumferences and BP in church-based studies [9,39,40] and CHOL in similar community interventions [41,42]. Thus, we also examine these clinical outcomes in this paper.…”
Section: Theoretical Perspectives and Review Of Literaturementioning
confidence: 98%
“…For body mass index of > 40 kg/m 2 , the annual likelihood of attaining normal weight was 1 in 1290 for men and 1 in 677 for women. Diet and activity programs are not sufficiently beneficial to alter these findings [26,27] . In a meta-analysis of 19 studies of weight reduction programs based on dietary changes and physical activity [27] , the mean weight loss was only 6.4 kg.…”
Section: Bariatric Surgery For the Treatment Of Nonalcoholic Fatty LImentioning
confidence: 99%
“…Weight loss does reduce hepatic steatosis, and loss of at least 3-5% of total body weight appears necessary to improve hepatic steatosis, but loss of up to 10% of total body weight may be necessary for improvement in NASH [5,23,24] . Diet and activity programs alone are usually insufficient [25][26][27] to result in the sustainable weight loss required to improve NASH in the morbidly obese. A recent nine year follow up junction and around the upper part of the stomach.…”
Section: Bariatric Surgery For the Treatment Of Nonalcoholic Fatty LImentioning
confidence: 99%